Miýo-pimātisiwin Developing Indigenous Cultural Responsiveness Theory (ICRT): Improving Indigenous Health and Well-Being - Sasakamoose, JoLee; Bellegarde, Terrina; Sutherland, Wilson; Pete, Shauneen; McKay-McNabb, Kim (International Indigenous Policy Journal, 2017)
The Truth and Reconciliation Commission of Canada calls upon those who can effect change within Canadian systems to recognize the value of Indigenous healing practices and to collaborate with Indigenous healers, Elders, and knowledge keepers where requested by Indigenous Peoples. This article presents the Indigenous Cultural Responsiveness Theory (ICRT) as a decolonized pathway designed to guide research that continuously improves the health, education, governance, and policies of Indigenous Peoples in Saskatchewan. Decolonizing practices include privileging and engaging in Indigenous philosophies, beliefs, practices, and values that counter colonialism and restore well-being. The ICRT supports the development of collaborative relationships between Indigenous Peoples and non-Indigenous allies who seek to improve the status of First Nations health and wellness.